The Effectiveness of Basic Physical Training Training in DKI Jakarta Sports Coaches - Hermanto; Eko Juli Fitrianto; Agung Robianto; Nadya Dwi Oktafiranda; Ela Yuliana (Jurnal Pendidikan Jasmani (JPJ), 2023)
This study aims to determine the effectiveness of basic physical exercise training for DKI Jakarta sports coaches. The research was conducted in May 2023. This data collection was carried out at the Faculty of Sports Science, State University of Jakarta by using stationery to fill out a questionnaire. The research method used is descriptive method with survey technique. This research instrument is a closed questionnaire and is distributed to the entire sample. The number of samples was 40 coaches who were the population of DKI Jakarta sports coaches. Based on the results of the research analysis, there is a significant difference between the pretest and posttest values in the overall research sample data with a significant value of pretest and posttest of 0.000 (p <0.05) so it can be concluded that there is an increase in the trainer's knowledge after attending basic physical training.